How is The Effectiveness of Ethnoscience-Based Modules in Science Learning in Indonesia?: A Systematic Literature Review - Ina Lestari; Zulirfan Zulirfan (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
This research aims to determine the effectiveness of ethnoscience-based science modules in Indonesia for junior high school students. The research method used is a systematic literature review using digital libraries, namely Google Scholar, Scopus, Eric, and Garuda. In this research, several stages were carried out, such as literature search strategies, selection procedures, data extraction, and data analysis. So that the selected literature is relevant, the search uses the keywords